Climate Risk Country Profile : Pakistan - World Bank Group; Asian Development Bank (World Bank, Washington, DC and Asian Development Bank, Manila, 2021)
Pakistan is characterized by diverse topography, ecosystems, and climate zones. Rich in natural resources, including fertile agricultural lands, natural gas reserves, and mineral deposits, Pakistan faces challenges in balancing competing objectives between economic development and environmental protection. This document aims to succinctly summarize the climate risks faced by Pakistan. This includes rapid onset and long-term changes in key climate parameters, as well as impacts of these changes on communities, livelihoods, and economies, many of which are already underway. This is a high-level synthesis of existing research and analyses, focusing on the geographic domain of Pakistan, therefore potentially excluding some international influences and localized impacts. The core data presented is sourced from the database sitting behind the World Bank Group’s (WBG) climate change knowledge portal (CCKP), incorporating climate projections from the Coupled Model Inter-comparison Project Phase 5 (CMIP5). This document is primarily meant for WBG and Asian Development Bank (ADB) staff to inform their climate actions and to direct readers to many useful sources of secondary data and research.